Massive Open Online Courses in Social Sciences and Their Implementation at Universities in Delhi: An Exploratory Study - Bhardwaj, Raj Kumar; Saxena, Vimal (DESIDOC Journal of Library & Information Technology, 2024)
Universities around the world have successfully incorporated Massive Open Online Courses (MOOCs) into their curricula and have facilitated credit transfers. The present study examines the integration of MOOCs in seven Indian universities. Moreover, the study focuses on the level of amalgamation of MOOCs, perceptions of institutions regarding the provision of online courses, and transition of MOOCs from informal to formal education. Furthermore, the study investigates the hindrances faced by higher educational institutions in providing services to MOOC learners. Purposive sampling technique was employed to facilitate selection of institutions. The responses were collected using a structured questionnaire. The study found moderate level, low level and very low-level integration of MOOCs in all seven universities. Six out of seven institutions namely, JNU, JMI, DU, GGSIPU, DBRAUD and NLU, adopted “Explain the perceived usefulness” as a strategy to influence the affordability uptake of MOOCs. Five out of seven institutions educate users about different MOOC platforms in the information literacy events. Surprisingly, two institution libraries out of seven revealed that their library services align with MOOCs. Surprisingly, majority of libraries of the seven institutions have not formulated any noteworthy strategy to foster the uptake of MOOCs among the academic community. Therefore, LIS professionals ought to grasp the nuances of various MOOC platforms. Also, library strategies should include MOOCs so that users can benefit.